The Judean Community within the Persian Imperial Framework: Insights from Biblical and Extrabiblical Sources: Ancient Jewish Memories of Achaemenid Persia 5 - Ganzel, Tova (Journal of Hebrew Scriptures, 2025)
This study examines the Judean community under Achaemenid Persian rule through a comparative reading of biblical texts and cuneiform sources. While cuneiform records document administrative and economic realities, biblical texts reflect theological interpretation and communal tensions. Together, they illuminate Judean interaction with Persian authority, temple practice, taxation, landholding, and the negotiation of identity within the imperial framework.